Determinants of Fraud Prevention in Islamic Banking: The Roles of Good Corporate Governance, Individual Morality, Organizational Culture, and Whistleblowing Systems - Nanda Suryadi; Muhammad Habib Ramadhan Z; Burhan Burhan; Ummu Ajrah Abdul Rauf (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Fraud remains a significant challenge for banking institutions as it can undermine financial performance, organisational sustainability, and public trust. This study aims to examine the effects of Good Corporate Governance (GCG), Individual Morality, Organisational Culture, and the Whistleblowing System on fraud prevention at Bank Riau Kepri Syariah, Pekanbaru Branch. A quantitative approach was employed using a saturated sampling technique involving 72 employees. Data were analysed using multiple linear regression with SPSS version 26. The results show that Good Corporate Governance, Organisational Culture, and the Whistleblowing System have a positive and significant effect on fraud prevention. In contrast, Individual Morality has a positive but statistically insignificant effect. The Whistleblowing System was found to be the most influential variable. The Adjusted R² value indicates that the independent variables explain 28% of the variation in fraud prevention, while the remaining 72% is explained by other factors outside the model. These findings suggest that strengthening governance practices, organisational culture, and whistleblowing mechanisms is essential for enhancing fraud prevention in Islamic banking institutions.